Pengaruh Budaya Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Tenaga Kerja Dan Transmigrasi (DISNAKERTRANS) Kabupaten Penajam Paser Utara - Muhid, Abdul; Rukaiyah, St; Suyuthi, Nurmadhani Fitria (STIM-LPI Makassar, 2024)
The purpose of this study is to determine and analyze the influence of work culture and work discipline on employee performance at the Department of Labor and Transmigration of North Penajam Paser. This study uses a quantitative method to assess the Influence of Work Culture and Work Discipline on Employee Performance at the Department of Labor and Transmigration of North Penajam Paser. Data were obtained from 42 employees using questionnaires and primary and secondary data sources. Data analysis used IBM SPSS Statistics, including classical assumption tests and multiple linear regression to evaluate variable influences. The results show that work culture has a positive and significant influence on employee performance, work discipline has a positive and significant relationship with employee performance, and work culture and work discipline together have a significant influence on employee performance. For research suggestions, as a strategy to maintain work culture and work discipline at the Department of Labor and Transmigration of North Penajam Paser, creating and implementing a reward or incentive system as a form of appreciation for employees who consistently demonstrate high commitment to work culture and work discipline. The reward system may include bonuses, public recognition, or career development opportunities as additional motivation for dedicated employees.